Designing an Innovative Educational Framework for “How We Live and Grow” Using the 4D Model - Utaminingsih, Esty Setyo; Intania, Belita Yoan; Aida, Hanik; Salama, Mahi Sultan; Sukma, Izza Melati (The Journal of Educational Development, 2024)
In the contemporary educational landscape, the need for effective and adaptable evaluation tools is increasingly critical. This study embarked on designing an innovative educational framework for the topic 'How We Live and Grow' using the Research and Development (R&D) method, articulated through the 4D model (Define, Design, Develop, and Disseminate). The objective was to develop a multifaceted instrument that supports primary education by bridging theoretical knowledge and practical application across cognitive domains from basic knowledge (C1) to creative synthesis (C6). The methodology involved collaborative design with educators, iterative development, and rigorous expert validation. Results showed that the framework successfully produced 20 multiple-choice questions, validated with high scores ranging from 86.25% to 91.25% by material and language experts, affirming the tool's reliability and educational value. This study not only enhanced the quality of teaching through tailored, context-relevant assessments but also contributed to educational research by developing a validated instrument that effectively measures and supports diverse cognitive skills in real-world settings. The framework's potential for broad application suggests a significant impact on shaping future educational practices and assessments.